The Relationship Between Staphylococcus Aureus Colonization in the Nose and Skin, and Atopic Dermatitis in Tishreen University Hospital outpatients. - Hassan, Fouz; Moalla, Mohammad; Harfouch, Nora (Latakia University Journal -Medical Sciences Series, 2019)
Atopic dermatitis (AD) is a common chronic inflammatory skin disorder that induces several symptoms including pruritus, dryness, and secondary cutaneous infections; its pathology is still poorly understood. Eventhough other skin diseases (such as psoriasis) share the same pathologic factor - skin barrier defect - with atopic dermatitis , patients diagnosed with those diseases don’t suffer infectious exacerbations as atopic patients do.This observational analytic study was conducted to compare staphylococcus aureus colonization rates and densities between atopic dermatitis patients and non-atopic subjects, and to relate the colonization to the severity and duration of disease.We found high rates and densities of colonization in lesional skin of patients, higher rates and densities of nasal colonization in AD patients compared to controls and detected a correlation between density of colonization and severity of eczema, but no correlation between density of colonization and duration of the disease.The high rates and densities of staphylococcus aureus colonization in lesional skin of atopic dermatitis patients point out the role of these organisms in the pathophysiology of the disease and explain infectious features in AD exacerbations التِهاب الجِلد التَّأَتُّبِيّ مَرَض التِهابِي جِلدِيّ مُزمِن شَائِع يَتَظَاهَر بِأَعرَاض مُتَعَدِّدَة: الحَكَّة – الجَفَاف وَالإِنتانات الجِلدِيَّة الثَّانَوِيَّة, ويُعتَبَر ذا آلِيَّة الإمرَاضِيَّة غَير وَاضِحة بِدِقَّة. عَلَى الرَّغم مِن أنَّ العديد مِن الأمراض الجِلديَّة (مثل الصُّداف) تَتَشارَك مَع التِهاب الجِلد التَّأتُّبِي بِوجود خَلَل في الحَاجِز الجِلدِيّ في الآليَّة الإمراضِيَّة, فإنَّ المرضى المُشَخَّصين بِتِلك الأمراض لا يعانون مِن مَظَاهِر إنتانيَّة مُرافِقة لِسَورات المَرَض لَدَيهم كَما هو الحال عند مرضَى التِهاب الجِلد التَّأَتُّبِي. هذه الدِّراسة التَّحليليَّة نَموذَج عيِّنة- شاهد أُجرِيَت لِمُقَارَنَة مُعَدَّلات وَكثافَة الاستِعمار الجرثومِيّ بِالعُنقودِيَّات المُذَهَّبَة بَين مَرضى التِهاب الجِلد التَّأتبُّي وَ الشَّواهِد غير التَّأتُّبيِّين, وَلِتَحرِّي العلاقَة بَينَ هذا الاستعمار وَبَينَ مُدَّة وَشِدَّة المَرَض. وَجدنا مُعَدَّلات وَكَثَافَات عَالِيَة لِلاستِعمَار في جِلد الآفَة لَدَى المرضَى, وَ مُعَدَّلات وَكثافات استِعمار أنفِيّ أَعلى لَدَى عيِّنة المَرضى نِسبَةً لِلشَّواهد, كما وَجَدنا ارتِبَاطاً بَينَ شِدَّة الإكزيما وَكَثَافَة الاستِعمار, دون وجود عَلَاقة بَينَ كَثَافَة الاستِعمَار وَمُدَّة الإِصابَة. إنَّ المُعَدَّلات وَالكَثافَات العَالِيَة للاستِعمَار بِالعنقودِيَّات المُذَهَّبِة في جِلد الآفات لِمَرضَى التِهاب الجِلد التَّأَتُّبِيّ يُوَجِّه نحوَ دَور هذه المُتَعَضِّيَات في الإِمرَاضِيَّة, وَيُفَسِّر المَظاهِر الإِنتانِيَّة المُرافِقَة لِسَوراتِها.